2008
DOI: 10.1016/s1472-6483(10)60413-0
|View full text |Cite
|
Sign up to set email alerts
|

Successful pregnancies after application of array-comparative genomic hybridization in PGS-aneuploidy screening

Abstract: Recurrent IVF failure, implantation failure and early embryo demise can be attributed to the high frequency of chromosomal aneuploidy observed in human embryos. Preimplantation genetic screening (PGS) using multiple displacement amplifications (MDA) and array comparative genomic hybridization (aCGH) was successfully performed on eight patients with a minimum of seven recurrent IVF failures with the aim of detecting aneuploidy and ameliorating pregnancy rate. A total of 41 embryos with eight or more cells were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
82
0
2

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(87 citation statements)
references
References 32 publications
2
82
0
2
Order By: Relevance
“…There are various PGS methods for comprehensive chromosome screening currently in clinical use, including comparative genomic hybridization (array-CGH) (4,5), single-nucleotide polymorphism (SNP) arrays (6-9), multiplex quantitative PCR (10), and next-generation sequencing (NGS) (11,12). Multiple clinical trials have confirmed the clinical efficacy of PGS, including increasing implantation and clinical pregnancy rates, as well as decreasing miscarriage rates (13)(14)(15)(16).…”
mentioning
confidence: 99%
“…There are various PGS methods for comprehensive chromosome screening currently in clinical use, including comparative genomic hybridization (array-CGH) (4,5), single-nucleotide polymorphism (SNP) arrays (6-9), multiplex quantitative PCR (10), and next-generation sequencing (NGS) (11,12). Multiple clinical trials have confirmed the clinical efficacy of PGS, including increasing implantation and clinical pregnancy rates, as well as decreasing miscarriage rates (13)(14)(15)(16).…”
mentioning
confidence: 99%
“…It has been proposed to investigate whether PGS does work if embryos are sampled at a slightly earlier or later stage (polar body and/or trophectoderm biopsy), but also to perform analyses using the broader testing options offered by array CGH. This is already being done in some clinics 84 and a multicentre trial has been set up by the European Society for Human Reproduction and Embryology (ESHRE) to determine the value of PGS based on polar-body biopsy and analysis with array CGH. 81 Using microarray PGS, targeted testing of chromosome regions and genes important to implantation and the odds of pregnancy can be performed.…”
Section: Pre-implantation Genetic Screeningmentioning
confidence: 99%
“…The PicoPlex ® library kit for WGA is a PCR-based technique that requires the fragmentation of large genomic DNA prior to the construction of a PCR-amplifiable library. Both MDA and PicoPlex ® methods for single-cell WGA have been used in array-based preimplantation testing (Hellani et al, 2008;Johnson et al, 2010; see Section 3.1).…”
Section: Techniques For Single-cell Whole-genome Amplificationmentioning
confidence: 99%